2021
DOI: 10.1002/app.50897
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thermal stability and gamma‐ray absorption in microwave absorbable poly(methyl methacrylate)/graphene nanoplatelets nanocomposite

Abstract: The graphene nanofiller (2 wt%) was dispersed in poly(methyl methacrylate) by in situ polymerization method. The optimum high frequency (microwave) absorption was evaluated at X‐band due to changes in the scattering parameters (determined by using a vector network analyzer). The slight improvement has been attained in gamma attenuation coefficient of the polymer nanocomposite by using gamma transmission technique. The addition of graphene nanoplatelets (2 wt%) resulted in a thermal improvement from 196.73 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…The mechanism that delays this diffusion and char formation has been described as the “tortuous path” effect of GNP. [ 5,43 ] Similar observations were observed for PA11/GNP [ 23 ] , PA11/expanded graphite, [ 32 ] and poly(methyl methacrylate)/GNP [ 44 ] nanocomposites.…”
Section: Resultssupporting
confidence: 77%
“…The mechanism that delays this diffusion and char formation has been described as the “tortuous path” effect of GNP. [ 5,43 ] Similar observations were observed for PA11/GNP [ 23 ] , PA11/expanded graphite, [ 32 ] and poly(methyl methacrylate)/GNP [ 44 ] nanocomposites.…”
Section: Resultssupporting
confidence: 77%
“…As presented in Table 3, the nanocomposite specimen containing 0.3 wt% aligned GONPs experienced the maximum thermal stability improvement compared with the neat epoxy. In addition, comparing the thermal stability results obtained from TGA with previous studies (e.g., 22,23 ) confirms that the alignment of GONPs is more suitable than their random distribution. GONPs with their two-dimensional structure, could act as effective heat conductors and transfer heat in the epoxy matrix during the decomposition of the nanocomposite.…”
Section: Conditionssupporting
confidence: 74%
“…They used the calendaring method to disperse 0.5 wt% GNPs in an epoxy resin and found that the degradation temperature of the nanocomposite was 20°C increased compared with the pure epoxy. Bel et al 23 studied the thermal stability of poly(methyl methacrylate)/graphene nanoplatelet nanocomposites. They reported that the addition of 2 wt% graphene nanoplatelets caused an improvement in decomposition temperature from 196.73 to 243°C at 5% weight loss in TGA analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Bel et al developed poly(methyl methacrylate)/graphene (PMMA/GNP) nanocomposites suitable for applications on the outside of electronic devices in commercial satellites [ 60 ]. These materials showed good thermal resistance, lightness, and gamma and microwave absorption properties.…”
Section: Thermal Stability Of Carbon-filled Polymer Composites For Sp...mentioning
confidence: 99%